Pengembangan Virtual Laboratory Berbasis HOTS dengan VBA Excel: Meningkatkan Pemahaman Konsep Suhu dan Kalor - Afifah Agustina; Fathiah Alatas; Dzikri Rahmat Romadhon (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
This research discusses the limited tools and rare temperature and heat experiments in high schools in Depok, which hinder students’ mastery of concepts and higher-order thinking skills (HOTS). This study proposes a virtual laboratory with VBA Excel that utilizes existing computer lab facilities and provides an effective and efficient way to learn physics1. The research method used is Research and Development (R&D) with the ADDIE model. Media and material experts validate the product, then tested by teachers and students using a tiered rating scale. The feasibility test scores from media experts are 93.61%, material experts 86.25%, and teacher responses 94.07%, with a very good interpretation. Furthermore, user trials were conducted with students, where one-on-one trials obtained a score of 90%, small group trials resulted in a score of 81.6% and field trials with a score of 81.48%. Based on the N-gain calculation, scores of 0.67 for small groups and 0.63 for field trials were obtained with moderate interpretation seen from the results of the pre-test and post-test scores calculation. Thus, it can be concluded that the virtual laboratory with VBA Excel on temperature and heat material can improve concept understanding and meet students' needs in higher-order thinking skills (HOTS).